Labial Melanotic Macules in Atopic Dermatitis: An Observational Study - Mohammed I Aljasser; Joseph Lam; Harvey Lui; Sunil Kalia (Wolters Kluwer Medknow Publications, 2019)
Background: Labial melanotic macules (LMMs) are benign hyperpigmented macules of unknown etiology. They can affect one or both lips. Their description in patients with atopic dermatitis (AD) is limited in the published literature. Objectives: The aim of the study was to describe the clinical characteristics of LMMs developing in Canadian patients with AD. Methods: This observational retrospective study was conducted in the period from November 2012 to March 2014. All patients with AD and lip pigmentation were included. Data collected included demographics and other information including AD clinical features, presence or absence of cheilitis, and lip pigmentation characteristics. Results: A total of 27 patients with LMMs and AD were enrolled. The condition was more common in females with a female: male ratio of 2.4:1. The median age at presentation was 16 years, and a majority of patients were Asian and had a prior history of cheilitis. There was a strong correlation between the duration of cheilitis and duration of LMMs (ρ =0.735, P= 0.001). Lesions presented as oval or round light-to-dark brown macules with a smooth border. The majority of patients (93%) had multiple LMMs and had involvement of both lips. Conclusion: Multiple LMMs are seen in Asian patients with AD and are associated with preceding cheilitis. LMMs secondary to AD should be considered among the differential diagnosis of lip pigmentation.